Relações entre capital humano, sistemas de previdência e aposentadoria - Untem, Andre Okamoto (2012)
In this work, we will present a series of general and partial equilibrium models that deals with human capital accummulation, social security systems, labor supply and retirement. We willanalyse the relations between different mechanisms of human capital accummulation and productivity; relations between uncertaints and hypothesis about credit markets; and the influence of those variables on households' decision of retirment.